2021
DOI: 10.3390/md19070401
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceuticals and Pharmaceuticals from Marine Fish and Invertebrates

Abstract: The word nutraceutical is coined from two words, “nutrition” and “pharmaceutical”, describing natural sources of molecules or substances that have physiological benefit, and the ability to protect human health and well-being and prevent chronic diseases [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In contrast to the traditionally low value attributed to fishery by-products, several studies have revealed that fish waste biomass holds immense potential as a rich source of high-value biomolecules such as functional components, nutraceuticals, and pharmaceuticals. [5][6][7][8][9][10][11][12] In this context, implementing a solid waste management strategy that involves recycling these byproducts into marketable products could be an effective solution. 13 Viscera, a significant by-product of the fisheries sector, possess immense potentiality as a valuable and cost-effective natural source of digestive proteases that display remarkable efficacy across a broad spectrum of temperature and pH.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the traditionally low value attributed to fishery by-products, several studies have revealed that fish waste biomass holds immense potential as a rich source of high-value biomolecules such as functional components, nutraceuticals, and pharmaceuticals. [5][6][7][8][9][10][11][12] In this context, implementing a solid waste management strategy that involves recycling these byproducts into marketable products could be an effective solution. 13 Viscera, a significant by-product of the fisheries sector, possess immense potentiality as a valuable and cost-effective natural source of digestive proteases that display remarkable efficacy across a broad spectrum of temperature and pH.…”
Section: Introductionmentioning
confidence: 99%
“…The massive diversification of organisms in the marine ecosystem serves as a reservoir of a wide range of natural compounds (1,2). New marine molecules and their biological potential are discovered every year, allowing these compounds to be used in functional foods and the development of new nutraceuticals and therapeutic drugs (3,4). In Asian countries, particularly China, Korea, and Japan, marine algae have long been consumed as food, whereas in Western countries, algae are mostly used as a source of food additives (5), natural pigment (6), and minerals (7).…”
Section: Introductionmentioning
confidence: 99%